Hyperpigmentation in photo exposed patches of vitiligo following tacrolimus therapy - Kanika Sahni; Vishal Gupta; Neena Khanna (Wolters Kluwer Medknow Publications, 2014)
Vitiligo is an acquired pigmentary disorder, clinically characterized by depigmented macules caused by destruction of melanocytes in the affected skin. Half of all patients develop the disease in childhood and adolescence before the age of 20 years, making vitiligo an important skin disease of childhood. There are numerous studies in the literature that suggest the efficacy of topical tacrolimus in vitiligo, without serious adverse effects. We describe a case of vitiligo in a pediatric patient who developed hyperpigmentation in the periorbital lesions of vitiligo with the use of topical tacrolimus. To the best of our knowledge, this is only the second such reported occurrence in a patient with vitiligo.